1989
DOI: 10.1139/z89-095
|View full text |Cite
|
Sign up to set email alerts
|

Demographic responses of arctic hares (Lepus timidus) to experimental reductions of red foxes (Vulpes vulpes) and martens (Martes martes)

Abstract: 1989. Demographic responses of arctic hares (Lepus timidus) to experimental reductions of red foxes (Vulpes vulpes) and martens (Martes murtes). Can. J. Zool. 67: 658 -668. This study aimed, through a field experiment, to test predictions from two hypotheses: (i) predation is a factor limiting arctic hare (Lepus timidus) populations, and (ii) predation shifts to arctic hares when voles (Microtus and Clethrionomys) decline to scarcity. Our approach was to compare demographic characteristics of hare populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 19 publications
0
51
0
Order By: Relevance
“…Impacts of predators on density and survival of alternative prey species as a result of a cyclic decline in another herbivore are often reported (e.g., Angelstam et al 1984;Sutherland 1988;Marcström et al 1989;Keith and Cary 1991;Korpimäki and Norrdahl 1991;Small and Keith 1992;Patterson et al 1998;Angerbjorn et al 1999). Keith and Cary (1991) inferred that increased predation may have occurred on populations of alternative prey (including Franklin's ground squirrels, Spermophilus franklinii) during a snowshoe hare population decline in Alberta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impacts of predators on density and survival of alternative prey species as a result of a cyclic decline in another herbivore are often reported (e.g., Angelstam et al 1984;Sutherland 1988;Marcström et al 1989;Keith and Cary 1991;Korpimäki and Norrdahl 1991;Small and Keith 1992;Patterson et al 1998;Angerbjorn et al 1999). Keith and Cary (1991) inferred that increased predation may have occurred on populations of alternative prey (including Franklin's ground squirrels, Spermophilus franklinii) during a snowshoe hare population decline in Alberta.…”
Section: Discussionmentioning
confidence: 99%
“…Steenhof and Kochert (1988) reported that Townsend's ground squirrels (Spermophilus townsendii) were alternative prey for golden eagles (Aquila chrysaetos) during a jackrabbit (Lepus californicus) decline in Idaho. Marcström et al (1989) concluded that arctic hare (Lepus timidus) population densities and growth rates declined in response to increased predation by red foxes (Vulpes vulpes) and martens (Martes martes), when populations of Microtus spp. and Clethrionomys spp.…”
Section: Discussionmentioning
confidence: 99%
“…Predation has been the primary proximate cause of mortality in cyclic mainland populations of snowshoe hares that have been monitored by telemetry (Hodges 2000). A number of studies of mountain hares (Lepus timidus) and brown hares (Lepus europaeus) on islands off the coast of Scandinavia have produced strong evidence that predation, or lack of it, is a major factor driving the dynamics of these island populations (Häkkinen and Jokinen 1981;Lindlöf and Lemnell 1981;Marcström et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Predator removal was usually associated with an increase in numbers in the autumn, but only 50% of 10 studies found an effect on breeding numbers. The effects are apparently more marked for hares, for which most studies found positive effects (Marcstrom et al 1989, Jensen 1970, Trautman et al 1974, Lindstrom et al 1994, Smedshaug et al 1999; but see Guthery & Beasom 1977, Kauhala et al 1999. In rabbits, results are more contrasting (Trautman et al 1974, Guthery & Beasom 1977, Newsome et al 1989).…”
Section: Effect Of Predator Control On Small Game Speciesmentioning
confidence: 98%